Phosphorus forms in forest soil colloids as revealed by liquid‐state 31P‐NMR1. Issue 2 (11th March 2016) - Missong, Anna; Bol, Roland; Willbold, Sabine; Siemens, Jan; Klumpp, Erwin
Abstract: Nanoparticles and colloids affect the storage and hence the availability of P in forest ecosystems. We investigated the fine colloids present in forest soils and their association with inorganic and organic P. To differentiate between the different P forms, we performed liquid‐state 31 P‐nucelar magnetic resonance ( 31 P‐NMR) measurements on forest bulk soil extracts, on colloid extracts and on the electrolyte phase of their soil suspensions. The 31 P‐NMR spectra indicated that soil nanoparticles and colloids were more enriched with organic than with inorganic P forms compared to the electrolyte phase. The P concentration was enriched in the colloidal fraction in comparison to the bulk soil and the phosphate diesters were more dominant in the colloidal fraction when compared to the bulk soil. The colloidal P‐diester to P‐monoester ratios were 2 to 3 times higher in the colloidal fraction than in the bulk soil. In contrast, relatively large percentages of inorganic P were found in the electrolyte phase. Supplementary (not shown) Data are available at the JuSER Server (juser.fz‐juelich.de, reference number: FZJ‐2016‐01739)https://juser.fz‐juelich.de/record/283057 .